Acute kidney injury following severe trauma: Risk factors and long-term outcome. Issue 3 (September 2015) - Eriksson, Mikael; Brattström, Olof; Mårtensson, Johan; Larsson, Emma; Oldner, Anders
Abstract : BACKGROUND: The trauma patient sustains numerous potentially harmful insults that may contribute to a notable risk of acute kidney injury (AKI). The aim of this study was to investigate the incidence of and to identify risk factors for AKI in severely injured trauma patients admitted to the intensive care unit (ICU). The patients were followed up for 1 year with respect to survival and end-stage renal disease. METHODS: Trauma patients admitted to the ICU for more than 24 hours at a Level I trauma center were included. The outcome measure was AKI diagnosed Days 2 to 7 of ICU treatment. Regression analysis was performed to identify factors associated with AKI development. RESULTS: A quarter of the patients (103 of 413) developed AKI within the first week of ICU admission. AKI was associated with increased 30-day (17.5% vs. 5.8%) and 1-year (26.2% vs. 7.1%) mortality. Risk factors for AKI were male sex, age, nondiabetic comorbidity, diabetes mellitus, Injury Severity Score (ISS) greater than 40, massive transfusion, and volume loading with hydroxyethyl starch (HES) within the first 24 hours. Unexpectedly, sepsis before AKI onset, admission hypotension, and extensive contrast loading (>150 mL) were not associated with AKI development. None of the surviving AKI patients had developed end-stage renal disease 1 year after injury. CONCLUSION: AKI in ICU-admitted trauma patients is a common complication with substantial mortality. Diabetes, male sex, and severe injury were strong risk factors, but age, nondiabetic comorbidity, massive transfusion, and resuscitation with HES were also associated with postinjury AKI. Based on the results of the current study, volume resuscitation with HES cannot be recommended in trauma patients. LEVEL OF EVIDENCE: Prognostic study, level III; therapeutic study, level IV.